2006
DOI: 10.1142/s021830130600496x
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Description of Nuclear Wobbling Motion Rotation of Triaxially Deformed Nuclei

Abstract: The nuclear wobbling motion in the Lu region is studied by the microscopic cranked mean-field plus RPA method. The Woods-Saxon potential is used as a mean-field with a new parameterization which gives reliable description of rapidly rotating nuclei. The prescription of symmetry-preserving residual interaction makes the calculation of the RPA step parameter-free, and we find the wobbling-like RPA solution if the triaxial deformation of the mean-field is suitably chosen. It is shown that the calculated outof-ban… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 18 publications
5
14
0
Order By: Relevance
“…It is seen that for the ISQQ interaction the sc triaxiality parameter γ ≈ 9 − 12 • is lower than +20 • suggested in Ref. [17], but close to the values found by Shoji and Shimizu [13] with Nilsson-Strutinsky minimization. The relative change of the deformation (ε, γ) to higher rotational frequencies is small.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is seen that for the ISQQ interaction the sc triaxiality parameter γ ≈ 9 − 12 • is lower than +20 • suggested in Ref. [17], but close to the values found by Shoji and Shimizu [13] with Nilsson-Strutinsky minimization. The relative change of the deformation (ε, γ) to higher rotational frequencies is small.…”
Section: Introductionsupporting
confidence: 83%
“…Nevertheless precise selfconsistency is required in the subsequent QRPA calculation in order to obtain reliable values for the excitation energies and E2/M1 properties of the wobbling band. As already noted in the previous QRPA papers [10][11][12][13][14], the absolute minimum of Ĥ corresponds to rotation about the short axis of the triaxial potential, along which the angular momentum of the i 13/2 proton is aligned (the sector of positive γ-values in standard Principle Axis Cranking (PAC) terminology). Above the frequency ω=0.5 MeV/ the PAC solution becomes unstable, because the moment of inertia of the medium axis is larger than the one of the short axis.…”
Section: Introductionmentioning
confidence: 96%
“…6 of Ref. [38]; although, the transition strength ratios were reproduced quite well in comparison to the experimentally determined values. From the discussion above, it is therefore concluded that, even though theoretical progress has been made, a complete description of the wobbling phenomenon in the lutetium/tantalum region remains a challenge that requires further investigation.…”
Section: Decreasing Wobbling Phonon Energysupporting
confidence: 65%
“…However, the wobbling energy was underestimated by nearly a factor of two at the lower frequencies, and predictions of the transition strength ratios were not nearly as satisfactory as those found using particle-rotor model methods. Shoji and Shimizu [38] performed random phase calculations based on a Woods-Saxon potential (rather than a Nilsson potential as in Refs. [32][33][34]) and were able to calculate a decreasing wobbling frequency for 163 Lu.…”
Section: Decreasing Wobbling Phonon Energymentioning
confidence: 99%
“…Section IV is devoted to the summary. A part of the present work was presented in some conference reports [42,43].…”
Section: Introductionmentioning
confidence: 99%